Cortisol, heart rate, and blood pressure as early markers of PTSD risk: A systematic review and meta-analysis. (November 2016) - Morris, Matthew C.; Hellman, Natalie; Abelson, James L.; Rao, Uma
Abstract: Individuals with posttraumatic stress disorder (PTSD) typically exhibit altered hypothalamic–pituitary-adrenal (HPA) function and sympathetic nervous system (SNS) activity. The goals of this study were to determine whether HPA and SNS alterations in the immediate aftermath of trauma predict subsequent PTSD symptom development and whether inconsistencies observed between studies can be explained by key demographic and methodological factors. This work informs secondary prevention of PTSD by identifying subgroups of trauma survivors at risk for PTSD. This meta-analysis (26 studies, N  = 5186 individuals) revealed that higher heart rate measured soon after trauma exposure was associated with higher PTSD symptoms subsequently ( r  = 0.13). Neither cortisol ( r  = − 0.07) nor blood pressure (diastolic: r  = − 0.01; systolic: r  = 0.02) were associated with PTSD symptoms which may be influenced by methodological limitations. Associations between risk markers (heart rate, cortisol, systolic blood pressure) and PTSD symptoms were in the positive direction for younger samples and negative direction for older samples. These findings extend developmental traumatology models of PTSD by revealing an age-related shift in the presentation of early risk markers. More work will be needed to identify risk markers and pathways to PTSD while addressing methodological limitations in order to shape and target preventive interventions. Highlights: Chronic PTSD is linked to alterations in major stress response systems. Neurobiological mechanisms of risk for developing PTSD are not well understood. A meta-analysis of 26 studies ( N  = 5186 individuals) was conducted. Higher heart rate predicted higher PTSD symptoms with a small effect size. Age of participants moderated associations between predictors and PTSD symptoms.